2014
DOI: 10.1155/2014/108562
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Selenium-Tolerant Rhizosphere Strain from a Novel Se-Hyperaccumulating PlantCardamine hupingshanesis

Abstract: A novel selenium- (Se-) hyperaccumulating plant, Cardamine hupingshanesis, accumulating Se as a form of SeCys2, was discovered in Enshi, Hubei, China, which could not be explained by present selenocysteine methyltransferase (SMT) theory. However, it is interesting to investigate if rhizosphere bacteria play some roles during SeCys2 accumulation. Here, one Se-tolerant rhizosphere strain, Microbacterium oxydans, was isolated from C. hupingshanesis. Phylogenetic analysis and 16S rRNA gene sequences determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Similar observations were reported by other authors. Brevibacterium frigoritolerans was in the same group with other Bacillus spp., i.e., B. simplex , B. muralis , B. psychrosaccharolyticus [ 20 , 21 , 22 ]. This bacterium can biosynthesize silver nanoparticles and tolerate silver as some Bacillus species can tolerate salt [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations were reported by other authors. Brevibacterium frigoritolerans was in the same group with other Bacillus spp., i.e., B. simplex , B. muralis , B. psychrosaccharolyticus [ 20 , 21 , 22 ]. This bacterium can biosynthesize silver nanoparticles and tolerate silver as some Bacillus species can tolerate salt [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…149,150 The rhizosphere of C. hupingshanensis harbors a Se-tolerant bacterium that can transfer Se (IV) into SeCys, indicating an important role of rhizosphere bacteria in Se hyperaccumulation by this plant species. 151 In contrast, an endophytic fungus that produces elemental Se was shown to be potentially involved in Se hyperaccumulation in A. bisulcatus. 150…”
Section: ■ Hyperaccumulators Of Other Elementsmentioning
confidence: 99%
“…This is remarkable, given that the two other well-studied Se hyperaccumulators (i.e., Astragalus bisulcatus and Stanleya pinnata) outside China were found to accumulate Se in their tissues mainly in the form of methylselenocysteine (approximately 70%). , The rhizosphere of C. hupingshanensis harbors a Se-tolerant bacterium that can transfer Se (IV) into SeCys, indicating an important role of rhizosphere bacteria in Se hyperaccumulation by this plant species . In contrast, an endophytic fungus that produces elemental Se was shown to be potentially involved in Se hyperaccumulation in A.…”
Section: Hyperaccumulators Of Other Elementsmentioning
confidence: 99%
“…Brevibacterium frigoritolerans as a novel organism can effectively degrade 89.81% of the residual phorate in soil [ 7 ]. It has also been reported that B. frigoritolerans can tolerate 5% NaCl stress, and greatly reduce the accumulation of Se in plants [ 8 ]. Nevertheless, there have been fewer studies of B. frigoritolerans as a salt-tolerant species capable of alleviating salt stress and promoting plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, B. frigoritolerans strain SMA23 is endowed with plant growth-promoting activities such as siderophore capacity, phosphate solubilization, and IAA production under abiotic stress at different temperatures [ 14 ]. B. frigoritolerans as a salt-tolerant microorganism has favorable salt tolerance [ 8 , 15 ], but there have been few studies on its application to promote plant growth under salt stress. Therefore, the plant growth-promoting activities of B. frigoritolerans under salt stress needed further study.…”
Section: Introductionmentioning
confidence: 99%